A Rare Cause of Acute Dysphagia: Abscess of the Base of the Tongue - Gulsum Teke Ozgur; Mehmet Volkan Akdogan; Gulhan Kanat Unler; Huseyin Savas Gokturk (Case Reports in Gastrointestinal Medicine)
Dysphagia represents a difficulty in passage of solid or liquid foods from the oral cavity into the stomach and is considered as an alarm symptom of gastrointestinal system. It often indicates an organic disease and needs to be explained. In this paper, a case of 61-year-old man with posterior tongue abscess is presented.